The Influence of Board Characteristics on Shareholders Assessment of Risk for Small and Large Firms: Evidence from Pakistan - Nazir, Muhammad Imran; Zulfiqar, Muhammad; Saeed, Muhammad Bilal; Habib, Yasir (International Journal of Economics and Financial Issues, 2016)
This unique study examines the alliance between board characteristics and shareholders assessment of risk as revealed in the volatility of stock returns for Pakistani listed companies. For this purpose, a sample of 30 manufacturing companies is used that are listed on Karachi Stock Exchange for the period of 2004 to 2013. The study uses panel data analysis and reports that random effect model is the best results yielding method. Our hypothesis incorporates preceding evidence that the small and large firms have spectacularly diverse constitution of boards, shimmering the firms diverse monitoring and counseling needs. It is hypothesized and locate confirmation with the intention of entrenched the large firms are able to produce affirmative net benefits, in the appearance of lesser risk, form board independence, gender diversity and director ownership. On the other hand the finding of this study showed the board size is negatively associated with the shareholder assessment of risk for large firms and the positive associated with the assessment of risk for small firms. The CEO duality is positive associated with the assessment of risk for large and negative associated amid assessment of risk for small firms. The results have insinuation for regulatory authorities, shareholders and directors to take steps to improve the board competanices for better performance. Keywords: Board Characteristics, Shareholders Assessment of Risk, Panel Data Analysis, Karachi Stock Exchange JEL Classifications: G32, G34, G38.